Method for qualitatively identifying printing thickening agent

By using the changes in viscosity and viscosity index in textile printing, combining hydrophobic association and physical crosslinking, the complexity and error of printing thickeners identification in the prior art are solved by using the changes in viscosity and viscosity index in the textile printing. The problem of high judgment rate has achieved rapid and accurate identification of composite pastes and is suitable for textile printing production.

CN119164830APending Publication Date: 2024-12-20HEBEI PROVINCIAL INST OF PROD QUALITY SUPERVISION & INSPECTION +3
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411071996.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-06
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

The identification method of printing thickeners in the prior art is complex, inconvenient to operate and lacks clear exclusivity, resulting in poor repeatability and high misjudgment rate of experimental results, making it difficult to accurately distinguish the components of the composite paste.

Method used

Using an indicator based on an associative multi-branched nonionic surfactant, the unsalted white paste and salted white paste are prepared, and the indicator is added to the test paste at different concentrations, using changes in viscosity and viscosity index. Qualitative identification was carried out, combining hydrophobic association and physical crosslinking to quickly distinguish composite pastes of polyacrylate, sodium carboxymethylcellulose or sodium alginate.

Benefits of technology

It realizes rapid and accurate identification of printing thickeners, simplifies the operation process, reduces the requirements of equipment conditions, improves the accuracy and repeatability of identification, and is suitable for textile printing production.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of quality evaluation, quality control and technical performance evaluation of textile chemicals, and discloses a qualitative identification method of a printing thickening agent. According to the method, a special indicator is adopted, and the indicator has better water dispersibility and good hydrophobic association capability based on a hydrophobic long chain, and provides an additional physical crosslinking structure for a test sample gel system; according to the technical method, the main composite components or categories of the main composite components of the sample can be qualitatively judged through the change of macroscopic application performance of the sample under the action of specified test conditions and indicators without carrying out complicated chemical analysis operation on the sample. In textile printing production practice, the technical method is suitable for distinguishing the polyacrylate thickening agent and the composite paste of the polyacrylate thickening agent and the sodium carboxymethyl cellulose or the composite paste of the polyacrylate thickening agent and the sodium alginate, so that a reasonable printing process is formulated, and the application prospect is good.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for identifying basic components of common textile printing pastes and the categories to which they belong, and in particular to a method for qualitative identification of printing thickeners. Background Art

[0002] In the production practice of textile printing, in order to give the printing paste excellent rheology, water retention, water holding capacity and clear and bright pattern transfer ability, polyacrylate thickeners, sodium alginate, sodium carboxymethyl cellulose and sodium carboxymethyl starch are the most common choices. However, these common printing thickeners have obvious shortcomings or defects in key application properties such as rheology, salt resistance and paste formation rate. Therefore, based on the concept of complementary advantages and the need to control production costs, polyacrylate thickeners and their composite pastes compounded with sodium alginate or sodium carboxymethyl cellulose have been rapidly developed and promoted. It should be pointed out that due to the significant differences in the physical and chemical properties of the composite paste and its interaction with fibers and dyes, there are also obvious differences in its printing effect and printed pattern style. Therefore, in production practice, it is necessary to prejudge the basic components of the selected printing thickener before the implementation of printing production in order to reasonably formulate printing technology and processes.

[0003] At present, the main methods for identifying the basic components of printing thickeners are:

[0004] 1. Identification method of basic components of printing thickener based on chemical color development reaction. This method uses a special chemical color developer to react with the hydrolysis product of the thickener under certain reaction conditions, and qualitatively identifies the basic chemical type of the thickener according to the different colors of the products.

[0005] For example, "Current Status and Analysis of Quality of Polyacrylic Acid Slurry (Cotton Textile Technology, Vol. 30, No. 8, 2002)" written by Cao Xuyong, Fan Xuerong, Rong Ruiping, etc. discloses a method of distinguishing the type of thickener through different color reactions of the hydrochloric acid hydrolyzate of the thickener with alkaline copper tartrate, iodine-boric acid, lanthanum nitrate and iodine reagent.

[0006] For example, the "Research Progress in Detection Methods of Sodium Carboxymethyl Cellulose in Food (China Food Industry, Issue 20, 2021)" written by Si Zhiwei, Zheng Siheng, Yan Jianheng, etc. discloses the color reaction of the acid hydrolyzate of sodium carboxymethyl cellulose with copper sulfate, anthraquinone, phenol, etc., to qualitatively or quantitatively determine its presence or content.

[0007] Compared with the instrumental analysis method, this method is relatively simple and easy to use, but it requires complicated operations such as acid hydrolysis, titration and color reaction control of the sample. The color reaction it relies on also has high requirements for the control of reaction conditions, and the repeatability of the experimental results is poor. At the same time, the experimental conclusions of this method require a combination of experiments on multiple color reactions to be drawn, and it does not have clear exclusivity. In addition, the colors of the products of different color reactions in this method are mostly in the same color system, and the judgment boundaries are not clear, which can easily lead to misjudgment.

[0008] 2. Identification method of basic components of printing thickener based on specific chemical reaction phenomenon. This method uses special chemical reagents to react with the treated samples after hydrolysis, coagulation, extraction, washing, digestion, dyeing, concentration and other special treatments. According to the changes in product color and reaction system state or by using analytical instruments to analyze the chemical structure of the extract, the basic chemical category of the thickener is qualitatively identified.

[0009] For example, "Qualitative Identification and Quantitative Determination of Modified Starch Slurry (Cotton Textile Technology, Vol. 26, No. 12, 1998)" written by Fan Xuerong, Gao Weidong, Rong Ruiping, etc. discloses a method for distinguishing the type of thickener based on the structural characteristics of various types of modified starch slurries and the differences in their physical and chemical properties to specific reactions.

[0010] Similarly, this method has a complicated operation process, high operation requirements, and usually requires a clear judgment of the basic composition of the sample, which is only suitable as a confirmatory discrimination method. At the same time, this method does not have clear exclusivity, and the judgment boundary based on the reaction phenomenon is not clear, which is easy to cause misjudgment.

[0011] 3. Based on the qualitative identification of chemical color development reaction and combined with the verification of specific chemical reaction phenomena, the identification method of the basic components of printing thickeners. This method aims at the problem that the color development method has poor exclusivity in the qualitative identification of thickeners. On the basis of the preliminary color development qualitative identification results, it is verified and confirmed by two or three different color development tests or its specific reaction phenomena to special reactants and specific reaction conditions, and the basic chemical types of thickeners are qualitatively identified.

[0012] For example, the identification of starch and polyvinyl alcohol (PVA) disclosed in "Rapid Identification Practice of Commonly Used Textile Slurries (Textile Guide, Issue 7, 2010)" written by Tong Yun uses the iodine-potassium iodide method for preliminary identification, and then verifies the sample category using the iodine-iodoboric acid method, the potassium dichromate method, and the difference in the thermal reversibility of the color development reactions of the two with iodine.

[0013] The above method requires further test methods to identify different slurries of the same category, such as various modified starches. The preparation and test methods of these reagents are relatively complicated and inconvenient to operate. In addition, this method cannot effectively distinguish heterogeneous thickeners with the same color reaction potential, that is, this method does not have clear exclusivity.

[0014] 4. Identification method of basic components of printing thickener based on professional analytical instruments. This method uses resonance Rayleigh scattering, gas chromatography / mass spectrometry, pyrolysis-gas chromatography / mass spectrometry, infrared spectroscopy and other instruments to separate and purify the samples, and qualitatively or quantitatively identify the basic chemical types and contents of the thickeners through the characteristic signals and their intensities presented by the samples on the instruments.

[0015] For example, the method of using resonance Rayleigh scattering method disclosed in "Research Progress on Detection Methods of Sodium Carboxymethyl Cellulose in Food (China Food Industry, Issue 20, 2021)" written by Si Zhiwei, Zheng Siheng, Yan Jianheng, etc., is to determine the presence of sodium carboxymethyl cellulose in samples such as synthetic water samples and tobacco that do not contain cationic surfactants by measuring the strong resonance Rayleigh scattering peak and its peak intensity produced by the ion-associated complex formed by the combination of sodium carboxymethyl cellulose and ethyl violet.

[0016] For example, in "Rapid Identification of Sizing Materials in Sized Fabrics Based on Py-GC / MS and NIRS (Master's Thesis of Zhejiang University of Technology 2023)" written by Li Xiaolian, thermal cracking, chromatography and mass spectrometry techniques are combined to crack sodium carboxymethyl cellulose into volatile small molecules. After gas chromatography separation, the characteristic cracking products are identified by mass spectrometry, thereby performing qualitative and quantitative analysis of the samples.

[0017] Instrumental analysis methods using resonance Rayleigh scattering, gas chromatography / mass spectrometry, and pyrolysis-gas chromatography / mass spectrometry have very high requirements for equipment conditions, and the sample preparation process is cumbersome, the sample preparation requirements are high, and the analysis conditions are harsh; at the same time, for mixed slurries, the absorption peaks of each component in the infrared spectrum may overlap or even be obscured, making it difficult to identify its components from the infrared spectrum. Summary of the invention

[0018] The purpose of the present invention is to overcome the problems of complicated experimental process, inconvenient operation and unclear exclusivity in the prior art, and provide a method for qualitative identification of printing thickeners. The indicator has good water dispersibility and good hydrophobic association ability based on hydrophobic long chains, and provides an additional "physical cross-linking" structure for the test sample gel system, resulting in significant changes in the main physical properties of different test sample gel systems. It is suitable for distinguishing polyacrylate thickeners and their composite pastes with sodium carboxymethyl cellulose or sodium alginate, so as to formulate a reasonable printing process, and has good application prospects.

[0019] In order to achieve the above object, the first aspect of the present invention provides a method for qualitative identification of a printing thickener, the method comprising the following steps:

[0020] (1) Preparing an indicator aqueous solution: subjecting a polyol, a fatty alcohol polyoxyethylene ether and a diisocyanate to an addition polymerization reaction, dissolving the resulting compound in soft water to prepare an indicator aqueous solution, wherein the diisocyanate is isophorone diisocyanate or toluene diisocyanate, wherein:

[0021] The indicator has the general structural formula (R1)R 1 (R2)(R3) or (R1)R 2 (R2)(R3)(R4) or (R1)R 3 (R2)(R3)(R4)(R5), where R 1 It is a triol or tetraol with a molecular weight of 50 to 150, R 2 It is a tetrahydric alcohol or pentahydric alcohol with a molecular weight of 100 to 200, R 3 It is a pentahydric alcohol or hexahydric alcohol with a molecular weight of 150 to 200, and R1, R2 and R3 have a general structural formula of RO-(CH2CH2O) n -H fatty alcohol polyoxyethylene ether, R is a saturated alkane with a carbon length of C12 to C14, n is an integer of 8 to 12, R4 is a polyethylene glycol chain segment with a molecular weight of 200 to 400 or the same as R1, R2, and R3, R5 is a polyethylene glycol chain segment with a molecular weight of 400 to 600, and R1, R2, R3, R4, and R5 are all connected to R 1 , R 2 , R 3 Connected,

[0022] In the addition polymerization reaction, the molar ratio of each polymerization monomer is the same as that shown in the general structural formula of the product.

[0023] The hydroxyl groups in R1, R2, R3, R4 and R5 react with diisocyanate by polyaddition reaction, so that R1, R2, R3, R4 and R5 block one isocyanate group in diisocyanate to obtain monoblocked diisocyanate, and then another isocyanate group on the monoblocked diisocyanate reacts with R 1 , R 2 , R 3 Carrying out a polyaddition reaction to obtain the indicator described in the present invention;

[0024] (2) preparing salt-free white paste and salt-containing white paste: dissolving the printing thickener to be tested in soft water and stirring thoroughly to prepare salt-free white paste; then adding inorganic salt to part of the salt-free white paste and stirring thoroughly to prepare salt-containing white paste;

[0025] (3) preparing a salt-free test paste and a salt-containing test paste: adding the indicator aqueous solution to the salt-free white paste and the salt-containing white paste respectively and stirring them sufficiently to prepare a salt-free test paste and a salt-containing test paste;

[0026] (4) Testing and qualitatively identifying the type of printing thickener: Testing the viscosity and viscosity index of salt-free white paste, salt-containing white paste, salt-free test paste, and salt-containing test paste, and comparing the changes in viscosity and viscosity index between salt-free test paste and salt-free white paste, as well as the changes in viscosity and viscosity index between salt-containing white paste and salt-containing test paste, to qualitatively determine the type of printing thickener.

[0027] Preferably, the polyol is selected from at least one of a trihydric alcohol, a tetrahydric alcohol, a pentahydric alcohol and a hexahydric alcohol.

[0028] Preferably, the printing thickener is polyacrylic acid salt, a composite paste A of polyacrylic acid salt and sodium carboxymethyl cellulose, or a composite paste B of polyacrylic acid salt and sodium alginate.

[0029] Preferably, the dry weight proportion of polyacrylic acid salt and sodium carboxymethyl cellulose in the composite paste A is not less than 30 weight %.

[0030] Preferably, the dry weight proportion of polyacrylic acid salt and sodium alginate in the composite paste B is not less than 30 weight %.

[0031] Preferably, the soft water is soft water with a total hardness of less than 30 ppm CaCO3.

[0032] Preferably, the solid content of the indicator aqueous solution is 50-70% by weight.

[0033] Preferably, the viscosity of the salt-free white paste is 3000±500 mPa.s.

[0034] Preferably, the salt content of the salt-containing white paste is 0.6±0.2% by weight.

[0035] Preferably, in step (3), salt-free test paste and salt-containing test paste of different concentrations are prepared respectively, wherein:

[0036] The preparation of salt-free test pastes of different concentrations includes: the amount of the indicator aqueous solution is 1.0±0.2 weight %, 2.0±0.3 weight %, 3.0±0.4 weight %, 4.0±0.5 weight %, 5.0±0.5 weight % of the amount of the salt-free white paste;

[0037] The preparation of salt test pastes of different concentrations includes: the dosage of the indicator aqueous solution is 1.0±0.2 weight %, 2.0±0.3 weight %, 3.0±0.4 weight %, 4.0±0.5 weight %, 5.0±0.5 weight % of the dosage of the salt white paste.

[0038] Preferably, the inorganic salt is sodium chloride.

[0039] Preferably, the inorganic salt is a chemically pure reagent.

[0040] Preferably, the step (4) specifically comprises:

[0041] (4.1) Testing the viscosity and viscosity index of salt-free white paste, salt-containing white paste, salt-free test pastes of different concentrations, and salt-containing test pastes of different concentrations, and obtaining the viscosity and viscosity index parameter values ​​thereof;

[0042] (4.2) Compare the viscosity of the salt-free test paste and the salt-free white paste of different concentrations. If the viscosity of the salt-free test paste is within the range of ±5% of the viscosity of the salt-free white paste, and the viscosity of the salt-containing white paste and the salt-containing test pastes of different concentrations is ≤500 mPa.s, then it is determined that the printing thickener is polyacrylate;

[0043] (4.3) comparing the viscosity and viscosity index of a salt-free test paste containing 2.0±0.3 wt% of an indicator aqueous solution with that of a salt-free white paste; if the viscosity and viscosity index of the salt-free test paste are both 120-150% of those of the salt-free white paste, and the viscosity of the salt-containing test paste is within the range of ±5% of the viscosity of the salt-containing white paste, then the printing thickener is determined to be a composite paste of polyacrylic acid salt and sodium carboxymethyl cellulose;

[0044] (4.4) Compare the viscosity and viscosity index of the salt-free test paste with an indicator aqueous solution content of 2.0±0.3% and the salt-free white paste. If the viscosity and viscosity index of the salt-free test paste are both 60-80% of the salt-free white paste, and the viscosity of the salt-containing test paste is 120-150% of the viscosity of the salt-containing white paste, then it is determined that the printing thickener is a composite paste of a polyacrylate thickener and sodium alginate.

[0045] Preferably, the viscosity and the viscosity index are measured at a test temperature of 25±5°C.

[0046] Compared with the prior art, the method of the present invention has at least the following advantages and characteristics:

[0047] 1. The present invention adopts "associative multi-branched nonionic surfactant" as a discrimination indicator for the composite paste of common polyacrylate thickener and sodium carboxymethyl cellulose or its composite paste with sodium alginate, and cleverly utilizes the difference in molecular weight, crosslinking degree, carboxyl substitution degree, etc. between sodium carboxymethyl cellulose and sodium alginate, which gives the gels of the two different response characteristics to the "hydrophobic association" of the indicator and the "ion shielding" effect of the electrolyte in terms of viscosity and rheological indexes, thereby realizing rapid and qualitative identification of the composite printing paste based on the two.

[0048] 2. The indicator used in the present invention has a special structure, has better water dispersibility and good hydrophobic association ability based on hydrophobic long chains, and provides an additional "physical cross-linking" structure for the test sample gel system. For sodium carboxymethyl cellulose and sodium alginate, which have significant differences in molecular weight, cross-linking degree, and carboxyl substitution degree, the hydrophobic association of the indicator and its additional "physical cross-linking" effect show significantly different or even completely opposite effects on its viscosity and rheological indexes under specially designed test conditions (test viscosity, indicator dosage, electrolyte dosage, etc.). Therefore, it is helpful to make accurate judgments.

[0049] 3. The present invention uses salt-free white paste and salt-containing white paste of the composite paste for testing. First, the category of the salt-free white paste of different samples is identified based on the "contradictory" response of the indicator in terms of viscosity and rheological indexes, which is simple and easy to judge with high accuracy; then, the category of the salt-containing white paste of different samples is verified based on the "differential" response of the indicator in terms of viscosity and rheological indexes, further improving the accuracy of sample identification.

[0050] 4. The identification method of the composite paste of polyacrylate thickener and sodium carboxymethyl cellulose or of the composite paste of polyacrylate thickener and sodium alginate does not require expensive professional instruments, and the operation process is simple and easy, with fewer uncontrollable factors, fast response and good repeatability. DETAILED DESCRIPTION

[0051] In order to further illustrate the present invention, the rapid qualitative identification method of the polyacrylate thickener and the composite paste thereof provided by the present invention is described in detail below in conjunction with the examples.

[0052] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0053] The method for qualitative identification of a printing thickener according to the present invention comprises the following steps:

[0054] (1) Preparing an indicator aqueous solution: subjecting a polyol, a fatty alcohol polyoxyethylene ether and a diisocyanate to an addition polymerization reaction, dissolving the resulting compound in soft water to prepare an indicator aqueous solution, wherein the diisocyanate is isophorone diisocyanate or toluene diisocyanate, wherein:

[0055] The indicator has the general structural formula (R1)R 1 (R2)(R3) or (R1)R 2(R2)(R3)(R4) or (R1)R 3 (R2)(R3)(R4)(R5), where R 1 It is a triol or tetraol with a molecular weight of 50 to 150, R 2 It is a tetrahydric alcohol or pentahydric alcohol with a molecular weight of 100 to 200, R 3 It is a pentahydric alcohol or hexahydric alcohol with a molecular weight of 150 to 200, and R1, R2 and R3 have a general structural formula of RO-(CH2CH2O) n -H fatty alcohol polyoxyethylene ether, R is a saturated alkane with a carbon length of C12 to C14, n is an integer of 8 to 12, R4 is a polyethylene glycol chain segment with a molecular weight of 200 to 400 or the same as R1, R2, and R3, R5 is a polyethylene glycol chain segment with a molecular weight of 400 to 600, and R1, R2, R3, R4, and R5 are all connected to R 1 , R 2 , R 3 Connected,

[0056] In the addition polymerization reaction, the molar ratio of each polymerization monomer is the same as that shown in the general structural formula of the product.

[0057] The hydroxyl groups in R1, R2, R3, R4 and R5 react with diisocyanate by polyaddition reaction, so that R1, R2, R3, R4 and R5 block one isocyanate group in diisocyanate to obtain monoblocked diisocyanate, and then another isocyanate group on the monoblocked diisocyanate reacts with R 1 , R 2 , R 3 Carrying out a polyaddition reaction to obtain the indicator described in the present invention;

[0058] (2) preparing salt-free white paste and salt-containing white paste: dissolving the printing thickener to be tested in soft water and stirring thoroughly to prepare salt-free white paste; then adding inorganic salt to part of the salt-free white paste and stirring thoroughly to prepare salt-containing white paste;

[0059] (3) preparing a salt-free test paste and a salt-containing test paste: adding the indicator aqueous solution to the salt-free white paste and the salt-containing white paste respectively and stirring them sufficiently to prepare a salt-free test paste and a salt-containing test paste;

[0060] (4) Testing and qualitatively identifying the type of printing thickener: Testing the viscosity and viscosity index of salt-free white paste, salt-containing white paste, salt-free test paste, and salt-containing test paste, and comparing the changes in viscosity and viscosity index between salt-free test paste and salt-free white paste, as well as the changes in viscosity and viscosity index between salt-containing white paste and salt-containing test paste, to qualitatively determine the type of printing thickener.

[0061] In the present invention, the indicator is a multi-branched compound. Due to the different numbers, lengths, hydrophilicity and flexibility of the branched chains, the multi-branched compound has different mutual associations in the aqueous system (mutual affinity and stability of the association structure) and different "hydrophobic association" effects with polyacrylic acid salt, sodium carboxymethyl cellulose or sodium alginate in the indicator. The more, longer and more flexible the hydrophobic branched chains are, the stronger the association ability is; the stronger the association ability and the better the association stability of the branched chains, the more obvious the effect on the viscosity and rheological indexes of polyacrylic acid salt, sodium carboxymethyl cellulose or sodium alginate.

[0062] In the present invention, the polyol may be at least one of a trihydric alcohol, a tetrahydric alcohol, a pentahydric alcohol and a hexahydric alcohol.

[0063] In the method described in the present invention, the process of the addition polymerization reaction may also include: reacting diisocyanate with fatty alcohol polyoxyethylene ether and polyethylene glycol at 75 to 90° C. and a catalyst for 60 to 120 minutes, preferably 80 to 85° C. and 80 to 100 minutes, to obtain a mono-blocked diisocyanate; then, reacting the mono-blocked diisocyanate with a polyol at 60 to 80° C. for 50 to 100 minutes, preferably 65 to 75° C. and 70 to 80 minutes, to obtain an indicator.

[0064] In a more preferred embodiment, the polyaddition reaction is carried out in the presence of a catalyst, and the catalyst may be at least one of stannous octoate and dibutyltin dilaurate, more preferably dibutyltin dilaurate.

[0065] In the method of the present invention, the printing thickener can be polyacrylic acid salt, a composite paste A of polyacrylic acid salt and sodium carboxymethyl cellulose, or a composite paste B of polyacrylic acid salt and sodium alginate.

[0066] In the present invention, the dry weight proportion of polyacrylic acid salt and sodium carboxymethyl cellulose in the composite paste A is not less than 30 weight %.

[0067] In the present invention, the dry weight proportion of polyacrylate and sodium alginate in the composite paste B is not less than 30 weight %.

[0068] In a more preferred embodiment, the soft water is soft water with a total hardness of less than 30 ppm CaCO3. In the present invention, if the CaCO3 content in the soft water is too high, it will affect the accuracy of the corresponding result of the indicator solution. In these preferred embodiments, the interference of CaCO3 in the water on the test result can be eliminated.

[0069] In the method of the present invention, the solid content of the indicator aqueous solution may be 50-70% by weight.

[0070] In the method of the present invention, the viscosity of the salt-free white paste may be 3000±500 mPa.s.

[0071] In the method of the present invention, the salt content of the salt-containing white paste may be 0.6±0.2% by weight.

[0072] In some embodiments, in step (3), salt-free test paste and salt-containing test paste of different concentrations are prepared respectively, wherein:

[0073] The preparation of salt-free test pastes of different concentrations includes: the amount of the indicator aqueous solution is 1.0±0.2 weight %, 2.0±0.3 weight %, 3.0±0.4 weight %, 4.0±0.5 weight %, 5.0±0.5 weight % of the amount of the salt-free white paste;

[0074] The preparation of salt test pastes of different concentrations includes: the dosage of the indicator aqueous solution is 1.0±0.2 weight %, 2.0±0.3 weight %, 3.0±0.4 weight %, 4.0±0.5 weight %, 5.0±0.5 weight % of the dosage of the salt white paste.

[0075] In the present invention, the inorganic salt is used to provide a certain ionic strength for the test, and is preferably sodium chloride.

[0076] In a more preferred embodiment, the inorganic salt is a chemically pure reagent.

[0077] In some embodiments, the step (4) further comprises:

[0078] (4.1) Testing the viscosity and viscosity index of salt-free white paste, salt-containing white paste, salt-free test pastes of different concentrations, and salt-containing test pastes of different concentrations, and obtaining the viscosity and viscosity index parameter values ​​thereof;

[0079] (4.2) Compare the viscosity of the salt-free test paste and the salt-free white paste of different concentrations. If the viscosity of the salt-free test paste is within the range of ±5% of the viscosity of the salt-free white paste, and the viscosity of the salt-containing white paste and the salt-containing test pastes of different concentrations is ≤500 mPa.s, then it is determined that the printing thickener is polyacrylate;

[0080] (4.3) comparing the viscosity and viscosity index of a salt-free test paste containing 2.0±0.3 wt% of an indicator aqueous solution with that of a salt-free white paste; if the viscosity and viscosity index of the salt-free test paste are both 120-150% of those of the salt-free white paste, and the viscosity of the salt-containing test paste is within the range of ±5% of the viscosity of the salt-containing white paste, then the printing thickener is determined to be a composite paste of polyacrylic acid salt and sodium carboxymethyl cellulose;

[0081] (4.4) Compare the viscosity and viscosity index of the salt-free test paste with an indicator aqueous solution content of 2.0±0.3% and the salt-free white paste. If the viscosity and viscosity index of the salt-free test paste are both 60-80% of the salt-free white paste, and the viscosity of the salt-containing test paste is 120-150% of the viscosity of the salt-containing white paste, then it is determined that the printing thickener is a composite paste of a polyacrylate thickener and sodium alginate.

[0082] In the present invention, due to the different structures (including physical structure and chemical structure) of the printing thickener and the indicator, and the different ionic strengths, molecular weights, water holding properties, water retention properties, self-association properties, and cross-association properties of pastes of different concentrations / viscosities, the types of the salt-free white pastes of different samples can be identified based on their "contradictory" responses to the indicator in terms of viscosity and rheological properties, which is simple and easy to judge with high accuracy; further, the types of the salt-containing white pastes of different samples can be verified based on their "differential" responses to the indicator in terms of viscosity and rheological properties, thereby further improving the accuracy of sample identification.

[0083] In the method of the present invention, the viscosity and the viscosity index are measured at a test temperature of 25±5°C.

[0084] In the present invention, by preparing salt-free test pastes and salt-containing test pastes with different indicator contents and making corresponding curves between test condition variables and macroscopic properties of the pastes, it is concluded that the viscosity and viscosity index of the salt-free test paste and the salt-free white paste with an indicator aqueous solution content of 2.0±0.3% by weight are the most obvious response indicators and the laws they exhibit are the most stable; at the same time, by repeatedly comparing the viscosities of the salt-free test paste and the salt-free white paste of different concentrations, the error of the qualitative identification result of the printing thickener can be reduced and the accuracy can be improved.

[0085] The following examples further illustrate the qualitative identification method of the printing thickener of the present invention. The examples are implemented on the premise of the technical solution of the present invention, and provide detailed implementation methods and specific operation processes, but the protection scope of the present invention is not limited to the following examples.

[0086] The experimental methods in the following examples, unless otherwise specified, are conventional methods in the art.

[0087] The remaining experimental materials used in the following examples, unless otherwise specified, are commercially available.

[0088] Example 1

[0089] (1) Step of preparing the indicator aqueous solution: In this step, a suitable amount of the indicator is mixed with soft water having a total hardness of less than 30 ppm CaCO3, and after sufficient stirring, an indicator aqueous solution having a solid content of 50% by weight is prepared. The indicator has the general structural formula (R1)R 1(R2)(R3), where R 1 is propylene glycol, R1, R2 and R3 are of the general structural formula RO-(CH2CH2O) n -H fatty alcohol polyoxyethylene ether with R=C12 and n=9;

[0090] The indicator is prepared by the following process: R1, R2, R3 and isophorone diisocyanate are subjected to polyaddition reaction for 90 to 100 minutes under the action of dibutyltin dilaurate as a catalyst at 75 to 80°C, so that the hydroxyl groups on the molecules of R1, R2 and R3 react with an isocyanate group on the isophorone diisocyanate molecule to prepare monoblocked isophorone diisocyanate, and then polyol R is added. 1 At 65-70°C, another isocyanate group on the mono-blocked isophorone diisocyanate is reacted with R 1 The hydroxyl groups on the molecule undergo addition polymerization for 60 to 70 minutes to obtain the indicator of the present invention;

[0091] (2) Preparation of salt-free white paste and salt-containing white paste: In this step, a proper amount of the printing thickener or printing paste to be tested is mixed with soft water having a total hardness of less than 30 ppm CaCO3, and stirred sufficiently to obtain 12 parts of salt-free white paste having a viscosity of 2900 to 3100 mPa·s; chemically pure sodium chloride having a mass percentage of 0.6 mPa·s% is added to 6 parts of the above salt-free white paste respectively and stirred sufficiently to obtain 6 parts of the corresponding salt-containing white paste;

[0092] (3) Preparation of salt-free test paste and salt-containing test paste: In this step, the indicator aqueous solution prepared in step (1) is added to 5 parts of salt-free white paste and 5 parts of salt-containing white paste prepared in step (2) in an amount of 1.0±0.1 weight %, 2.0±0.1 weight %, 3.0±0.2 weight %, 4.0±0.2 weight % and 5.0±0.3 weight % to the mass of the salt-free white paste and the salt-containing white paste, respectively, and the mixture is stirred sufficiently to prepare 5 parts of salt-free test paste and 5 parts of salt-containing test paste of the sample;

[0093] (4) Steps for qualitative identification of sample types: Compare the changes in viscosity and viscosity index between the salt-free test paste and the salt-free white paste, and between the salt-containing test paste and the salt-containing white paste, and qualitatively determine the type of the printing thickener or printing paste sample to be tested, specifically:

[0094] (4.1) Testing the viscosity and viscosity index of 1 salt-free white paste, 1 salt-containing white paste, 5 salt-free test pastes, and 5 salt-containing test pastes, and obtaining the viscosity and viscosity index parameter values ​​thereof;

[0095] (4.2) Compare the viscosity of the five salt-free test pastes with that of the salt-free white paste. If the viscosity of the former is within the range of ±5% of the viscosity of the salt-free white paste, and the viscosity of the salt-containing white paste and the five salt-containing test pastes is ≤200 mPa·s, then the sample can be qualitatively determined to be a polyacrylate thickener;

[0096] (4.3) Compare the viscosity and viscosity index of the test paste with an indicator content of 2.0±0.1 wt % and the white paste. If the viscosity and viscosity index of the salt-free test paste are both 120-150% of those of the salt-free white paste, it can be qualitatively determined that the sample is a composite paste of polyacrylic acid salt thickener and sodium carboxymethyl cellulose;

[0097] (4.4) Compare the viscosity and viscosity index of the test paste with an indicator content of 2.0±0.1 wt % and the white paste. If the viscosity and viscosity index of the salt-free test paste are both 60-80% of those of the salt-free white paste, it can be qualitatively determined that the sample is a composite paste of polyacrylate thickener and sodium alginate.

[0098] Example 2

[0099] (1) Step of preparing the indicator aqueous solution: In this step, a proper amount of the indicator is mixed with soft water having a total hardness of less than 30 ppm CaCO3, and after sufficient stirring, an indicator aqueous solution having a solid content of 60% by weight is prepared. The indicator has the general structural formula (R1)R 2 (R2)(R3)(R4), where R 2 is pentaerythritol, R1, R2 and R3 are of the general structural formula RO-(CH2CH2O) n -H fatty alcohol polyoxyethylene ether, wherein R=C12, n=9, and R4 is a polyethylene glycol chain segment with a molecular weight of 200;

[0100] The indicator is prepared by the following process: R1, R2, R3, R4 and isophorone diisocyanate are subjected to polyaddition reaction at 80-85°C and under the action of a catalyst, dibutyltin dilaurate, for 90-100 minutes, so that the hydroxyl groups on the molecules of R1, R2, R3, R4 react with an isocyanate group on the isophorone diisocyanate molecule to prepare a mono-blocked isophorone diisocyanate, and then a polyol R is added. 2 At 70-75°C, another isocyanate group on the mono-blocked isophorone diisocyanate is reacted with R 2 The hydroxyl groups on the molecule undergo addition polymerization for 70 to 80 minutes to obtain the indicator of the present invention;

[0101] (2) Preparation of salt-free white paste and salt-containing white paste: In this step, an appropriate amount of the printing thickener or printing paste to be tested is mixed with soft water having a total hardness of less than 30 ppm CaCO3, and stirred sufficiently to obtain 12 parts of salt-free white paste having a viscosity of 2800 to 3200 mPa·s; 0.6±0.1 wt % of chemically pure sodium chloride is added to 6 parts of the salt-free white paste respectively and stirred sufficiently to obtain 6 parts of the corresponding salt-containing white paste;

[0102] (3) Preparation of salt-free test paste and salt-containing test paste: In this step, the indicator aqueous solution prepared in step (1) is added to 5 parts of salt-free white paste and 5 parts of salt-containing white paste prepared in step (2) in an amount of 1.0±0.1 weight %, 2.0±0.2 weight %, 3.0±0.2 weight %, 4.0±0.3 weight % and 5.0±0.4 weight % to the mass of the salt-free white paste and the salt-containing white paste, respectively, and the mixture is stirred sufficiently to prepare 5 parts of salt-free test paste and 5 parts of salt-containing test paste of the sample;

[0103] (4) Steps for qualitative identification of sample types: Compare the changes in viscosity and viscosity index between the salt-free test paste and the salt-free white paste, and between the salt-containing test paste and the salt-containing white paste, and qualitatively determine the type of the printing thickener or printing paste sample to be tested, specifically:

[0104] (4.1) Testing the viscosity and viscosity index of 1 salt-free white paste, 1 salt-containing white paste, 5 salt-free test pastes, and 5 salt-containing test pastes, and obtaining the viscosity and viscosity index parameter values ​​thereof;

[0105] (4.2) Compare the viscosity of the five salt-free test pastes with that of the salt-free white paste. If the viscosity of the former is within the range of ±5% of the viscosity of the salt-free white paste, and the viscosity of the salt-containing white paste and the five salt-containing test pastes is ≤300 mPa·s, then the sample can be qualitatively determined to be a polyacrylate thickener;

[0106] (4.3) Compare the viscosity and viscosity index of the test paste with an indicator content of 2.0±0.2 wt % and the white paste. If the viscosity and viscosity index of the salt-free test paste are both 120-150% of those of the salt-free white paste, it can be qualitatively determined that the sample is a composite paste of polyacrylic acid salt thickener and sodium carboxymethyl cellulose;

[0107] (4.4) Compare the viscosity and viscosity index of the test paste with an indicator content of 2.0±0.2 wt % and the white paste. If the viscosity and viscosity index of the salt-free test paste are both 60-80% of those of the salt-free white paste, it can be qualitatively determined that the sample is a composite paste of polyacrylate thickener and sodium alginate.

[0108] Example 3

[0109] (1) Step of preparing the indicator aqueous solution: In this step, a suitable amount of the indicator is mixed with soft water having a total hardness of less than 30 ppm CaCO3, and after sufficient stirring, an indicator aqueous solution having a solid content of 70% by weight is prepared. The indicator has the general structural formula (R1)R 3 (R2)(R3)(R4)(R5), where R 3 It is pentylene pentol, and R1, R2 and R3 have the general structural formula RO-(CH2CH2O) n -H fatty alcohol polyoxyethylene ether with R=C14, n=12, R4 is a polyethylene glycol chain segment with a molecular weight of 200, and R5 is a polyethylene glycol chain segment with a molecular weight of 400;

[0110] The indicator is prepared by the following process: R1, R2, R3, R4, R5 and isophorone diisocyanate are subjected to polyaddition reaction for 110 to 120 minutes under the action of dibutyltin dilaurate as a catalyst at 85 to 90° C., so that the hydroxyl groups on the molecules of R1, R2, R3, R4, R5 react with an isocyanate group on the isophorone diisocyanate molecule to prepare monoblocked isophorone diisocyanate, and then polyol R is added. 3 At 75-80°C, another isocyanate group on the mono-blocked isophorone diisocyanate is reacted with R 3 The hydroxyl groups on the molecule undergo addition polymerization for 80 to 90 minutes to obtain the indicator of the present invention;

[0111] (2) Preparation of salt-free white paste and salt-containing white paste: In this step, a proper amount of the printing thickener or printing paste to be tested is mixed with soft water having a total hardness of less than 30 ppm CaCO3, and stirred sufficiently to obtain 12 parts of salt-free white paste having a viscosity of 3200 to 3400 mPa·s; 0.5 to 0.7 weight % of chemically pure sodium chloride is added to 6 parts of the salt-free white paste respectively and stirred sufficiently to obtain 6 parts of the corresponding salt-containing white paste;

[0112] (3) Preparation of salt-free test paste and salt-containing test paste: In this step, the indicator aqueous solution prepared in step (1) is added to 5 parts of salt-free white paste and 5 parts of salt-containing white paste prepared in step (2) in an amount of 1.0±0.1 weight %, 2.0±0.2 weight %, 3.0±0.3 weight %, 4.0±0.4 weight % and 5.0±0.5 weight % to the mass of the salt-free white paste and the salt-containing white paste, respectively, and the mixture is stirred sufficiently to prepare 5 parts of salt-free test paste and 5 parts of salt-containing test paste of the sample;

[0113] (4) Steps for qualitative identification of sample types: Compare the changes in viscosity and viscosity index between the salt-free test paste and the salt-free white paste, and between the salt-containing test paste and the salt-containing white paste, and qualitatively determine the type of the printing thickener or printing paste sample to be tested, specifically:

[0114] (4.1) Testing the viscosity and viscosity index of 1 salt-free white paste, 1 salt-containing white paste, 5 salt-free test pastes, and 5 salt-containing test pastes, and obtaining the viscosity and viscosity index parameter values ​​thereof;

[0115] (4.2) Compare the viscosity of the five salt-free test pastes with that of the salt-free white paste. If the viscosity of the former is within the range of ±5% of the viscosity of the salt-free white paste, and the viscosity of the salt-containing white paste and the five salt-containing test pastes is ≤400 mPa·s, then it can be qualitatively determined that the sample is a polyacrylate thickener;

[0116] (4.3) Compare the viscosity and viscosity index of the test paste with an indicator content of 2.0±0.2 wt % and the white paste. If the viscosity and viscosity index of the salt-free test paste are both 120-150% of those of the salt-free white paste, it can be qualitatively determined that the sample is a composite paste of polyacrylic acid salt thickener and sodium carboxymethyl cellulose;

[0117] (4.4) Compare the viscosity and viscosity index of the test paste with an indicator content of 2.0±0.2 wt % and the white paste. If the viscosity and viscosity index of the salt-free test paste are both 60-80% of those of the salt-free white paste, it can be qualitatively determined that the sample is a composite paste of polyacrylate thickener and sodium alginate.

[0118] It can be seen from the above examples that, compared with traditional chemical or instrumental analysis methods, the technical method of the present invention can quickly and qualitatively identify the main composite components of the sample or the category to which it belongs within 30 minutes with the assistance of a viscometer, which is simple, easy to operate and has a high accuracy rate.

[0119] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A method for qualitative identification of printing thickeners, It is characterized in that The method comprises the following steps: (1) Preparing an indicator aqueous solution: subjecting a polyol, a fatty alcohol polyoxyethylene ether and a diisocyanate to an addition polymerization reaction, dissolving the resulting compound in soft water to prepare an indicator aqueous solution, wherein the diisocyanate is isophorone diisocyanate or toluene diisocyanate, wherein: The general structural formula of the indicator is (R 1 )R 1 (R 2 )(R 3 ) or (R 1 )R 2 (R 2 )(R 3 )(R 4 ) or (R 1 )R 3 (R 2 )(R 3 )(R 4 )(R 5 ), where R 1 It is a triol or tetraol with a molecular weight of 50 to 150, R 2 It is a tetrahydric alcohol or pentahydric alcohol with a molecular weight of 100 to 200, R 3 It is a pentahydric alcohol or hexahydric alcohol with a molecular weight of 150 to 200, R 1 , R 2 and R 3 The general structural formula is RO-(CH 2 CH 2 O) n -H fatty alcohol polyoxyethylene ether, R is a saturated alkane with a carbon length of C12 to C14, n is an integer of 8 to 12, R 4 A polyethylene glycol chain with a molecular weight of 200 to 400 or R 1 , R 2 , R 3 Same, R 5 is a polyethylene glycol chain with a molecular weight of 400 to 600, R 1 , R 2 , R 3 , R 4 , R 5 Both are connected to R 1 , R 2 , R 3 Connected, In the addition polymerization reaction, the molar ratio of each polymerization monomer is the same as that shown in the general structural formula of the product, R 1 , R 2 , R 3 , R 4 , R 5 The hydroxyl groups in the ester react with diisocyanate to make R 1 , R 2 , R 3 , R 4 , R 5 One isocyanate group in the diisocyanate is blocked to obtain a mono-blocked diisocyanate, and then another isocyanate group on the mono-blocked diisocyanate is bonded to R 1 , R 2 , R 3 Carrying out a polyaddition reaction to obtain the indicator described in the present invention; (2) preparing salt-free white paste and salt-containing white paste: dissolving the printing thickener to be tested in soft water and stirring thoroughly to prepare salt-free white paste; then adding inorganic salt to part of the salt-free white paste and stirring thoroughly to prepare salt-containing white paste; (3) preparing a salt-free test paste and a salt-containing test paste: adding the indicator aqueous solution to the salt-free white paste and the salt-containing white paste respectively and stirring them sufficiently to prepare a salt-free test paste and a salt-containing test paste; (4) Testing and qualitatively identifying the type of printing thickener: Testing the viscosity and viscosity index of salt-free white paste, salt-containing white paste, salt-free test paste, and salt-containing test paste, and comparing the changes in viscosity and viscosity index between salt-free test paste and salt-free white paste, as well as the changes in viscosity and viscosity index between salt-containing white paste and salt-containing test paste, to qualitatively determine the type of printing thickener.

2. The method according to claim 1, It is characterized in that The polyol is selected from at least one of trihydric alcohol, tetrahydric alcohol, pentahydric alcohol and hexahydric alcohol.

3. The method according to claim 1, It is characterized in that The printing thickener is polyacrylic acid salt, a composite paste A of polyacrylic acid salt and sodium carboxymethyl cellulose, or a composite paste B of polyacrylic acid salt and sodium alginate; Preferably, the dry weight proportion of polyacrylic acid salt and sodium carboxymethyl cellulose in the composite paste A is not less than 30 weight %; Preferably, the dry weight proportion of polyacrylic acid salt and sodium alginate in the composite paste B is not less than 30 weight %.

4. The method according to any one of claims 1 to 3, It is characterized in that The soft water has a total hardness of less than 30ppm CaCO 3 of soft water.

5. The method according to any one of claims 1 to 4, It is characterized in that The solid content of the indicator aqueous solution is 50-70% by weight.

6. The method according to claim 1, It is characterized in that The viscosity of the salt-free white paste is 3000±500 mPa·s; Preferably, the salt content of the salt-containing white paste is 0.6±0.2% by weight.

7. The method according to any one of claims 1 to 6, It is characterized in that In step (3), salt-free test paste and salt-containing test paste of different concentrations are prepared respectively, wherein: The preparation of salt-free test pastes of different concentrations includes: the amount of the indicator aqueous solution is 1.0±0.2 weight %, 2.0±0.3 weight %, 3.0±0.4 weight %, 4.0±0.5 weight %, 5.0±0.5 weight % of the amount of the salt-free white paste; The preparation of salt test pastes of different concentrations includes: the dosage of the indicator aqueous solution is 1.0±0.2 weight %, 2.0±0.3 weight %, 3.0±0.4 weight %, 4.0±0.5 weight %, 5.0±0.5 weight % of the dosage of the salt white paste.

8. The method according to claim 1 or 7, It is characterized in that The inorganic salt is sodium chloride; Preferably, the inorganic salt is a chemically pure reagent.

9. The method according to any one of claims 1 to 8, It is characterized in that The step (4) specifically comprises: (4.1) Testing the viscosity and viscosity index of salt-free white paste, salt-containing white paste, salt-free test pastes of different concentrations, and salt-containing test pastes of different concentrations, and obtaining the viscosity and viscosity index parameter values ​​thereof; (4.2) Compare the viscosity of the salt-free test paste and the salt-free white paste of different concentrations. If the viscosity of the salt-free test paste is within the range of ±5% of the viscosity of the salt-free white paste, and the viscosity of the salt-containing white paste and the salt-containing test pastes of different concentrations is ≤500 mPa·s, then the printing thickener is determined to be polyacrylate; (4.3) comparing the viscosity and viscosity index of a salt-free test paste containing 2.0±0.3 wt% of an indicator aqueous solution with that of a salt-free white paste; if the viscosity and viscosity index of the salt-free test paste are both 120-150% of those of the salt-free white paste, and the viscosity of the salt-containing test paste is within the range of ±5% of the viscosity of the salt-containing white paste, then the printing thickener is determined to be a composite paste of polyacrylic acid salt and sodium carboxymethyl cellulose; (4.4) Compare the viscosity and viscosity index of the salt-free test paste with an indicator aqueous solution content of 2.0±0.3% and the salt-free white paste. If the viscosity and viscosity index of the salt-free test paste are both 60-80% of the salt-free white paste, and the viscosity of the salt-containing test paste is 120-150% of the viscosity of the salt-containing white paste, then it is determined that the printing thickener is a composite paste of a polyacrylate thickener and sodium alginate.

10. The method according to any one of claims 1, 6 and 9, It is characterized in that The viscosity and the viscosity index are measured at a test temperature of 25±5°C.